Application of different techniques on stone fruit (Prunus spp.) drying and assessment of physical, chemical and biological properties: Characterization of dried fruit properties. Issue 2 (23rd December 2020) - Vakula, Anita; Tepić Horecki, Aleksandra; Pavlić, Branimir; Jokanović, Marija; Ognjanov, Vladislav; Milović, Maja; Teslić, Nemanja; Parpinello, Giuseppina; Decleer, Marlies; Šumić, Zdravko
Abstract: Drying of stone fruit with different techniques and characterization of physical, chemical and biological properties of convective dried, vacuum dried and lyophilised stone fruit, as well as analysing and structuring the data sets by principal component analysis (PCA) were obtained in this paper. Drying technique significantly influenced the shear force, hardness, springiness and cohesiveness of dried apricot NS4 (Novi Sad 4) samples ( p  < .05); the total phenolic, flavonoid and monomeric anthocyanin content of dried sour cherry Feketicka, sweet cherry Lapins, sweet cherry Sweet Heart and plum Toptase samples and also the antioxidant capacity of dried sour cherry Feketicka, plum Anna Spath and peach Lela samples. The most noticeable differentiations of the stone fruit groups of samples dried with convective and vacuum drying and lyophilisation were observed in raw and dried sour cherry Feketicka and Erdi Botermo samples. Practical applications: The results and conclusions obtained in this research have various application in food industry in many aspects. First, part of the fruit varieties investigated in this study were developed at the Faculty of Agriculture and their application in the fruit drying industry has been thoroughly investigated. In addition, application of different drying techniques on different stone fruit species were applied in this research. Finally, the possibilities of preservation the most important quality indicators of dried fruit was observed. The impact of obtained conclusions and results in the field of agricultural and food industry is significant, since they could be applied in the industrial processes.